2021
DOI: 10.3389/fneur.2021.618269
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and VNG Features in Anterior Canal BPPV—An Analysis of 13 Cases

Abstract: Objective: To define diagnostic VNG features in anterior canal BPPV during positional testing (Dix-Hallpike, supine head hanging, and McClure Pagnini tests).Study Design: A retrospective study of patients diagnosed with anterior canal BPPV across four referral centers in New Delhi, Kochi, Bangalore, and Dubai.Subjects and Methods: Clinical records of 13 patients with AC BPPV out of 1,350 cases, during a 3-years period, were reviewed and analyzed by four specialists.Results: Four patients had positional down be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…One clue suggesting hc-BPPV is that on Dix-Hallpike testing, the patient has definite symptoms but the Therefore, if the downbeating nystagmus is persistent (continues as long as the patient is in the position) or does not respond to positional treatment, then it is safest to consult neurology and/or perform magnetic resonance imaging (MRI) in suspected BPPV patients with downbeating nystagmus. 49,50 Wrong "PPV"…”
Section: Wrong Canalmentioning
confidence: 99%
“…One clue suggesting hc-BPPV is that on Dix-Hallpike testing, the patient has definite symptoms but the Therefore, if the downbeating nystagmus is persistent (continues as long as the patient is in the position) or does not respond to positional treatment, then it is safest to consult neurology and/or perform magnetic resonance imaging (MRI) in suspected BPPV patients with downbeating nystagmus. 49,50 Wrong "PPV"…”
Section: Wrong Canalmentioning
confidence: 99%
“…In the first two Dix-Hallpike (DH) maneuvers the torsional component was consistently to the right (affected) side regardless of the vertical component. As discussed in the video report (1), the spatial orientation of both superior canals (about 108 closer to the sagittal plane than the PC) increases the likelihood that SC-BPPV could be equally provoked in both the DH maneuver and the Head Hanging maneuver (2)(3)(4), again in the left SC BPPV the torsional component could be absent or beat to the left side instead of to the right. In right aPC BPPV the torsional component should beat to the left (rather than right), as in this case.…”
Section: Author Response: Re: Benign Paroxysmal Positionalvertigo: Ca...mentioning
confidence: 99%
“…Studies have shown that nystagmus, an involuntary, rapid, and rhythmic movement of the eyeball, has a close coupling relationship with BPPV [2,3]. Therefore, the analysis of abnormal eye movement information is of great significance in diagnosing BPPV.…”
Section: Introductionmentioning
confidence: 99%